Recurrent pyometra and xanthogranulomatous salpingitis: A rare pathologic association in a postmenopausal lady - Neha Gami; Rajlaxmi Mundhra; Kiran Guleria; Vinod Kumar Arora; Shipra Garg (Journal of Mid-Life Health, 2014)
Xanthogranulomatous inflammation is a rare, non-neoplastic variant of chronic inflammation. Of the 15 reported cases of Xanthogranulomatous endometritis, majority (60%) were accompanied by endometrial carcinoma. We herein report a case of a postmenopausal woman presenting with recurrent pyometra who was suspected to be case of cervical tuberculosis and treated for the same. Inspite of antitubercular therapy, she had cervical stenosis and developed recurrent pyometra over the next 2 years requiring repeated drainage. She then underwent hysterectomy and was found to have co-existent Xanthogranulomatous salpingitis (XGS) on histopathological examination. Xanthogranulomatous inflammation is a rare pathological diagnosis that gynecologists need to be aware of while managing such patients.